Finding non-classical critical nuclei and minimum energy path of Cu precipitates in Fe–Cu alloys. (27th October 2017) - Li, Boyan; Zhang, Lei; Li, Chengliang; Li, Qiulin; Chen, Jun; Shu, Guogang; Weng, Yuqing; Xu, Ben; Liu, Wei
Abstract: For most steels, the aging- or radiation-induced hardenability of Cu precipitates has been concerned for many years. Experiments show that Fe–Cu alloys undergo aging- or radiation- induced phase separation into Cu-rich precipitates, resulting in property degradation processes. In this work, we developed a model integrating constrained string method and phase-field approaches to investigate the non-classical critical nuclei and minimum energy path of Cu precipitates. The Fe–Cu binary alloy is taken as a model system. The free energies used in the phase-field model are from CALPHAD. The simulation results demonstrated that the formation of Cu stable clusters undergo an energy barrier and the predicted thermodynamic properties of the critical nucleus which are related to temperature and Cu overall concentration, in good agreement with the theoretical calculation as well as experimental observations.